Wet process method of multilayer ceramic device

KR103032299B1Active Publication Date: 2026-10-13KOREA ELECTROTECH RES INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020220092001
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-07-25
Publication Date
2026-10-13
Estimated Expiration
2042-07-25

Smart Images

  • Figure 112022077745323-PAT00001_ABST
    Figure 112022077745323-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a wet manufacturing method for a stacked ceramic element. The technical gist of the present invention is to comprise the steps of: manufacturing a ceramic laminate having a metal oxide and preparing a base solution having a pH of 5 to 12 by mixing a chloride with an aqueous solvent; preparing a wet solution by adding hydrazine hydrate (N2H4·H2O) and the ceramic laminate to the base solution; and reducing the metal oxide to a metal by stirring the wet solution at 60 to 100°C for up to 12 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a wet manufacturing method for a stacked ceramic element. Background Technology

[0002] Ceramic devices offer fast response and precision, and can be made small and lightweight, which expands their applications in micro-displacement control devices, valves, and pumps; however, they show limitations due to their smaller displacement compared to electric devices. To overcome this, stacked ceramic devices are being developed by stacking multiple layers of thin ceramics with electrodes formed thereon.

[0003] Multilayer ceramic devices are manufactured by first forming ceramic materials into thin ceramic forms, forming electrodes with a conductive material on the surface of the ceramics, and then stacking multiple layers; since the stacked ceramics have low strength, they are hardened through heat treatment.

[0004] The prior art document "Ceramic device using metal oxide and method for manufacturing the same (KR 10-2020-0033167 A)" discloses forming a core-shell powder composed of a core made of a metal oxide and a shell made of metal that surrounds the core, coating glass on the surface of the core-shell powder and then forming an electrode paste by mixing with a binder, printing the electrode paste onto a ceramic tape and then laminating it to form a ceramic laminate, and subsequently performing a first heat treatment of the ceramic laminate under an oxidizing atmosphere and then performing a second heat treatment under a reducing atmosphere containing hydrogen.

[0005] As such, the prior art literature aimed to provide a ceramic device with increased electrical conductivity by using a metal oxide to prevent shrinkage and expansion of the electrode so that the metal does not oxidize during heat treatment, and by finally reducing the metal oxide to a metal having a nanoporous structure.

[0006] However, as in the aforementioned prior art literature, if dry heat treatment is performed in air or an inert atmosphere rather than heat treatment in a solution, the following problems arise.

[0007] First of all, dry heat treatment fundamentally requires large furnace equipment that occupies a significant amount of workspace. Furthermore, since the dry reaction of metal oxides involves the use of large amounts of hydrogen and the maintenance of high-temperature processes for extended periods, substantial costs are inevitably incurred, making mass production difficult.

[0008] In addition, although dry heat treatment can be a reliable process for ferroelectric ceramics that rely on the thermodynamics and reaction kinetics between the ceramic and the inert gas hydrogen, some piezoelectric ceramics cause stability problems, such as easily exploding in an inert gas atmosphere above 300°C.

[0009] Therefore, there is a need for technology to improve process stability by utilizing a process other than dry heat treatment for stacked ceramic devices. Accordingly, the inventors, taking note of the above technical requirements, developed a method to easily reduce metal oxides of internal electrodes to metals through wet heat treatment in a solution, thereby enabling mass production of stacked ceramic devices, and completed the present invention. Prior art literature

[0010] (Patent Document 0001) KR 10-2020-0033167 A The problem to be solved

[0011] The present invention was developed to resolve the above-mentioned problems, and the technical problem is to provide a wet manufacturing method for a stacked ceramic device that achieves process stability and enables mass production by easily reducing the metal oxide of an internal electrode to metal through wet heat treatment in a solution. means of solving the problem

[0012] To solve the above technical problem, the present invention provides a wet manufacturing method for a multilayer ceramic element, characterized by comprising: a step of manufacturing a ceramic laminate having a metal oxide and mixing a chloride with an aqueous solvent to prepare a base solution having a pH of 5 to 12; a step of preparing a wet solution by adding hydrazine hydrate (N2H4·H2O) and the ceramic laminate to the base solution; and a step of reducing the metal oxide to a metal by stirring the wet solution at 60 to 100°C for up to 12 hours.

[0013] In the present invention, the ceramic laminate is characterized by being manufactured through the steps of: applying an electrode paste, prepared by mixing a metal with a binder, onto a PZT-based ceramic substrate to produce a ceramic sheet and stacking a plurality of said ceramic sheets; and degreasing and sintering the plurality of stacked ceramic sheets so that the metal oxidizes and forms a metal oxide.

[0014] In the present invention, the wet solution is characterized by being prepared by adding the hydrazine hydrate in a range of 0.01 to 10 moles based on 1 mole of the metal oxide.

[0015] In the present invention, the chloride is characterized as being one or more of sodium chloride (NaCl), potassium chloride (KCl), lithium chloride (LiCl), calcium chloride (CaCl2), and barium chloride (BaCl2).

[0016] In the present invention, following the step of reducing to the metal, the method further comprises the step of separating the ceramic laminate from the wet solution and then washing and drying. Effects of the invention

[0017] According to the present invention, which is a means for solving the above problem, by heat-treating a ceramic laminate equipped with a metal oxide in a solution through a wet process, the problem of increased costs associated with the use of a large amount of inert gas and maintaining a high-temperature process for a long time during conventional dry heat treatment is resolved, thereby enabling mass production.

[0018] In addition, the wet manufacturing method of the present invention is based on an aqueous solvent, and since only water-based residues remain after wet heat treatment in the solution, it has excellent effects in terms of the environment. Brief explanation of the drawing

[0019] FIG. 1 is a schematic diagram showing a wet manufacturing method for a stacked ceramic element according to the present invention. Figure 2 is a photograph showing the wet manufacturing method of a stacked ceramic element according to the present invention in sequence. Figure 3 is a comparative photograph of a metal oxide before reduction and a metal after reduction through a wet process according to the present invention. Figure 4 shows an internal electrode photograph and an SEM photograph before and after reduction according to Example 1. Figure 5 is a comparison photograph of the internal electrode when the time is changed while the wet process temperature according to Example 1 is fixed at 100 ℃. Figure 6 is a graph of kinetics according to pH change. Specific details for implementing the invention

[0020] The present invention is capable of various modifications and may take various forms, and embodiments are to be described in detail in the text. However, this is not intended to limit the present invention to the specific disclosed forms, and it should be understood that it includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the invention.

[0021] Throughout the specification, when a part is described as "including" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0022] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this specification.

[0023] The terms used in this specification are used merely to describe specific embodiments and are not intended to limit the invention. Singular expressions include plural expressions unless the context clearly indicates otherwise.

[0024] The present invention relates to a wet manufacturing method for a stacked ceramic element. In this regard, referring to FIG. 1, which shows a schematic diagram of a wet manufacturing method for a stacked ceramic element according to the present invention, and FIG. 2, which shows a photograph of a wet manufacturing method for a stacked ceramic element according to the present invention in sequence, the method comprises the steps of: manufacturing a ceramic stack provided with a metal oxide and preparing a base solution having a pH of 5 to 12 by mixing a chloride with an aqueous solvent (S10); preparing a wet solution by adding hydrazine hydrate (N2H4·H2O) and the ceramic stack to the base solution (S20); and reducing the metal oxide to a metal by stirring the wet solution at 60 to 100°C for up to 12 hours (S30).

[0025] However, the ceramic laminate described in this specification refers to a ceramic element before performing a wet process, and the stacked ceramic element refers to a ceramic element after performing a wet process.

[0026] According to the wet manufacturing method of the above-described stacked ceramic element, first, a ceramic stack provided with a metal oxide is manufactured, and a base solution having a pH of 5 to 12 is prepared by mixing a chloride in an aqueous solvent separately from the ceramic stack (S10).

[0027] A ceramic laminate can be manufactured by applying an electrode paste, prepared by mixing a metal with a binder, onto a PZT-based ceramic substrate to produce a ceramic sheet, stacking multiple ceramic sheets, and then degreasing and sintering the layers to form a metal oxide as the metal oxidizes. The metal oxide formed at this time can serve as an internal electrode of the ceramic laminate.

[0028] PZT-based ceramics are ceramic materials widely used in the field of electronic ceramics due to their high dielectric constant and piezoelectric properties, and can be composed of PZT (lead zirconate titanate), PMN-PZT (lead magnesium niobate-lead zirconate titanate), PNN-PZT (lead nickel niobate-lead zirconate titanate), or mixtures thereof.

[0029] The metal in the electrode paste serves as the electrode material. Before proceeding with the explanation, silver (Ag) has a very low melting point of 961°C and is therefore not suitable for use in PZT-based ceramics, which require high sintering temperatures. Consequently, it is dissolved in solid solution with palladium (Pd) or platinum (Pt), which have higher melting points, to form silver-palladium (AgPd) or silver-platinum (AgPt). However, since precious metals like palladium are very expensive, the proportion of relatively inexpensive silver is increased to use it as an electrode material; despite this, economic reasons have posed a critical obstacle to the mass production of multilayer ceramic devices. Consequently, copper and nickel have begun to be used as electrode materials in place of silver-palladium. Copper has the advantage of being an inexpensive non-precious metal that can be applied to internal electrodes, but during degreasing and sintering, a portion of the copper oxidizes and transforms into copper oxide. In the case of nickel, while it is somewhat more expensive than copper, it is cheaper than silver-palladium.

[0030] Alternatively, a copper composite compound prepared by the following method may be used as the metal for the electrode paste. To this end, copper and heterogeneous element nanoparticles are first wet-mixed to produce a core-shell powder in which the copper is positioned as the core and the heterogeneous element nanoparticles are coated as a shell on the outside of the copper. The core-shell powder is heat-treated in an inert gas atmosphere to produce an alloyed powder in which the heterogeneous element nanoparticles penetrate and diffuse into the interior of the copper. Subsequently, the alloy powder is exposed to an oxygen atmosphere to cool and then milled to produce an oxide powder containing oxygen with a size of 0.01 to 1 μm. Then, the oxide powder is heat-treated in a hydrogen atmosphere to reduce the oxide powder, causing the oxygen and hydrogen to combine and evaporate, thereby producing a copper composite compound in which the oxide powder crystallizes.

[0031] A binder forms a physical bond with a metal to form an electrode paste, and α-terpinol, etc., can be used. That is, an electrode paste prepared by mixing a metal with a binder is applied along the pattern of the portion where the internal electrode is formed on the surface of a PZT-based ceramic substrate, and a ceramic laminate is manufactured by repeating the process of stacking a PZT-based ceramic substrate on top of it and applying the electrode paste.

[0032] Apart from the ceramic laminate, a base solution is prepared by mixing a chloride as in Fig. 2(b) with an aqueous solvent as in the photograph of Fig. 2(a) to adjust the pH to 5 to 12.

[0033] The aqueous solvent is a water-based solvent, which may be distilled water or ultrapure water, and in the case of chloride, it may be one or more of sodium chloride (NaCl), potassium chloride (KCl), lithium chloride (LiCl), calcium chloride (CaCl2), and barium chloride (BaCl2).

[0034] The chloride can be mixed in an amount ranging from 10 to 50 g per 1 L of the above aqueous solvent. If the chloride is less than 10 g or exceeds 50 g, it becomes difficult to create an environment where the metal oxide is subsequently reduced to a metal, and it becomes difficult to adjust the pH to 5 to 12, preferably 7 to 12.

[0035] Next, a wet solution is prepared by adding hydrazine hydrate (N2H4·H2O) and a ceramic laminate to the base solution (S20).

[0036] As shown in Fig. 2(c), hydrazine hydrate can be introduced into the base solution first instead of the ceramic laminate, and then the ceramic laminate can be introduced as shown in Fig. 2(d). However, in Fig. 2(d), the metal oxide of the internal electrode of the ceramic laminate is copper oxide (Cu2O).

[0037] In some cases, the ceramic laminate may be added to the prepared base solution first, followed by the addition of hydrazine hydrate. Since hydrazine hydrate plays a role in reducing metal oxides to metals, caution is required because adding it first to the base solution may cause process inconvenience, as it may necessitate adding additional hydrazine hydrate or using additives to lower the pH in order to balance the reduction of the metal oxide content.

[0038] In other words, when a ceramic laminate is manufactured, the metal forming the internal electrode of the ceramic laminate inevitably undergoes oxidation into a metal oxide during the degreasing and sintering processes, and this must be reduced back to a metal. Accordingly, hydrazine hydrate is added to a base solution in which a chloride is mixed with an aqueous solvent and adjusted to a pH of 5 to 12 to induce the reduction of the metal oxide back to a metal.

[0039] It is preferable to mix hydrazine hydrate in a range of 0.01 to 10 moles based on 1 mole of metal oxide to reduce metal oxides in ceramic laminates to metals. If the amount of hydrazine hydrate is less than 0.01 moles, it may take a long time to reduce metal oxides to metals, resulting in negligible reduction efficiency, and if it exceeds 10 moles, it will not be possible to maintain the stable state of PZT-based ceramics.

[0040] Next, the wet solution is stirred at 60 to 100 ℃ for up to 12 hours to reduce the metal oxide of the internal electrode to metal, and the PZT-based ceramic is maintained in a stabilized state (S30).

[0041] The wet solution is a state in which a ceramic laminate is impregnated in a solution composed of an aqueous solvent, chloride, and hydrazine hydrate, and can be sealed as in FIG. 2(e), left to stand for a certain period of time, and then heated using a drying oven as in FIG. 2(f) for up to 12 hours.

[0042] Heat treatment in a wet solution can be set or heated to a temperature range from 60°C to 100°C. If the temperature is below 60°C, it takes more than 12 hours to completely reduce the metal oxide to the metal, and if it exceeds 100°C, it goes into a high-temperature range, so process stability cannot be improved, which entails high costs for mass production.

[0043] Regarding time, the reduction of metal oxides to metal may occur as soon as the temperature is set to 60 to 100°C after forming the wet solution, but it may also occur within an appropriate range depending on the environment within a maximum of 12 hours.

[0044] Ultrasonic vibration may be applied when stirring the wet solution at 60 to 100°C for up to 12 hours. This is to increase the stirring power of the wet solution and increase the reduction rate of the metal oxide.

[0045] The metal oxide of the ceramic laminate manufactured according to the above-described wet manufacturing method can undergo a reduction reaction to metal as shown in Reaction Scheme 1 below, and Reaction Scheme 1 is as follows.

[0046] [Reaction Equation 1]

[0047] 2Cu2O + N2H4→ 2N2+ H2O + 4Cu

[0048] As shown in reaction equation 1 above, when hydrazine hydrate is added to a wet solution containing copper oxide, which is a metal oxide forming the internal electrode of a ceramic laminate, it can be confirmed that the oxide film on the surface of the copper oxide reacts with the hydrazine hydrate and is removed, thereby reducing it to metallic copper.

[0049] Finally, the ceramic laminate is separated from the wet solution, then washed and dried (S40).

[0050] After the reduction from metal oxide to metal is completed, the ceramic laminate is separated from the wet solution and finished through washing and drying processes.

[0051] Figure 3 is a photograph comparing the metal oxide before reduction according to the present invention with the metal after reduction through a wet process. Referring to Figure 3(a), copper oxide (Cu2O), which is the metal oxide before reduction through the wet process, is visible. In Figure 3(b), it is confirmed that the copper oxide has turned into an orange-red color, which is the natural color of copper (Cu), through a wet process involving heat treatment in a solution. Thus, it can be confirmed that the reduction of copper oxide to copper is stably achieved.

[0052] The embodiments of the present invention will be described in more detail below. However, the following embodiments are provided merely to aid in understanding the present invention and do not limit the scope of the present invention.

[0053] <Preparation Example 1>

[0054] An electrode paste was prepared by mixing copper powder with α-terpinol in a weight ratio of 6:4. The prepared electrode paste was applied along an electrode pattern to the portion of an internal electrode space formed on the surface of a PZT-based ceramic substrate, and then the binder contained in the electrode paste was degreased by binder burnout at 550°C in an atmospheric atmosphere, and then the copper in the electrode paste and the PZT ceramic were sintered at 1,150°C to produce a ceramic laminate.

[0055] <Preparation Example 2>

[0056] A core-shell powder was prepared by wet-mixing 10 μm copper particles and 40 nm nickel particles in a weight ratio of 9:1 to coat the surface of the copper particles with nickel particles. The prepared core-shell powder was heat-treated at 700 °C in a mixed gas atmosphere of nitrogen and hydrogen to produce an alloy powder in which copper and nickel were alloyed. Subsequently, the alloy powder was cooled by exposing it to an oxygen atmosphere and then milled using zirconia balls for 12 hours to produce a fine oxide powder with a size of 0.1 to 1 μm. The fine oxide powder was heated at 400 °C in a hydrogen atmosphere, causing oxygen and hydrogen to combine and evaporate into vapor, while the remaining metals crystallized to produce a copper composite compound.

[0057] An electrode paste was prepared by mixing the copper composite compound prepared above with α-terpinol in a weight ratio of 6:4. The prepared electrode paste was applied along an electrode pattern to the portion where an internal electrode space was formed on the surface of a PZT-based ceramic substrate, and then the binder contained in the electrode paste was degreased by binder burnout at 550 °C in an atmospheric atmosphere, and then the copper of the electrode paste and the PZT ceramic were sintered at 1,150 °C to produce a ceramic laminate.

[0058] <Example 1>

[0059] A base solution with a pH of 12 was prepared by adding 1.5 g of NaOH to 0.05 L of DI water. 3.6 g of hydrazine hydrate (N2H4·H2O) was mixed into the base solution, and a wet solution was prepared by adding the ceramic laminate prepared in Preparation Example 1. Subsequently, the wet solution was stirred at 100 ℃ for 8 hours, and the ceramic laminate was separated from the wet solution to produce a final multilayer ceramic device through washing and drying.

[0060] <Example 2>

[0061] A base solution with a pH of 7 was prepared by adding 1.5 g of NaOH to 0.05 L of DI water. 3.6 g of hydrazine hydrate (N2H4·H2O) was mixed into the base solution, and a wet solution was prepared by adding the ceramic laminate prepared in Preparation Example 1. Subsequently, the wet solution was stirred at 100 ℃ for 8 hours, and the ceramic laminate was separated from the wet solution to produce a final multilayer ceramic element through washing and drying.

[0062] <Example 3>

[0063] A base solution with a pH of 12 was prepared by adding 1.5 g of NaOH to 0.05 L of DI water. 3.6 g of hydrazine hydrate (N2H4·H2O) was mixed into the base solution, and a wet solution was prepared by adding the ceramic laminate prepared in Preparation Example 1. Subsequently, the wet solution was stirred at 80°C for 8 hours, and the ceramic laminate was separated from the wet solution to produce a final multilayer ceramic element through washing and drying.

[0064] <Example 4>

[0065] A base solution with a pH of 7 was prepared by adding 1.5 g of NaOH to 0.05 L of DI water. 3.6 g of hydrazine hydrate (N2H4·H2O) was mixed into the base solution, and a wet solution was prepared by adding the ceramic laminate prepared in Preparation Example 1. Subsequently, the wet solution was stirred at 80°C for 3 hours, and the ceramic laminate was separated from the wet solution to produce a final multilayer ceramic element through washing and drying.

[0066] <Example 5>

[0067] A base solution with a pH of 12 was prepared by adding 1.5 g of NaOH to 0.05 L of DI water. 3.6 g of hydrazine hydrate (N2H4·H2O) was mixed into the base solution, and a wet solution was prepared by adding the ceramic laminate prepared in Preparation Example 1. Subsequently, the wet solution was stirred at 60°C for 8 hours, and the ceramic laminate was separated from the wet solution to produce a final multilayer ceramic element through washing and drying.

[0068] <Example 6>

[0069] A base solution with a pH of 7 was prepared by adding 1.5 g of NaOH to 0.05 L of DI water. 3.6 g of hydrazine hydrate (N2H4·H2O) was mixed into the base solution, and a wet solution was prepared by adding the ceramic laminate prepared in Preparation Example 1. Subsequently, the wet solution was stirred at 60°C for 4 hours, and the ceramic laminate was separated from the wet solution to produce a final multilayer ceramic device through washing and drying.

[0070] <Comparative Example 1>

[0071] A base solution with a pH of 12 was prepared by adding 1.5 g of NaOH to 0.05 L of DI water. 3.6 g of hydrazine hydrate (N2H4·H2O) was mixed into the base solution, and a wet solution was prepared by adding the ceramic laminate prepared in Preparation Example 1. Subsequently, the wet solution was stirred at 40°C for 4 hours, and the ceramic laminate was separated from the wet solution to produce a final multilayer ceramic element through washing and drying.

[0072] <Comparative Example 2>

[0073] A base solution with a pH of 12 was prepared by adding 1.5 g of NaOH to 0.05 L of DI water. 3.6 g of hydrazine hydrate (N2H4·H2O) was mixed into the base solution, and a wet solution was prepared by adding the ceramic laminate prepared in Preparation Example 1. Subsequently, the wet solution was stirred at 25°C for 12 hours, and the ceramic laminate was separated from the wet solution to produce a final multilayer ceramic element through washing and drying.

[0074] The wet process conditions of Examples 1 to 6 and Comparative Examples 1 and 2, and the degree of stabilization of the state of the PZT-based ceramic substrate and internal electrode after reduction were confirmed and are shown in Table 1 below.

[0075] temperature hour pH electrode surface electrode inside ceramic Example 1 100 ℃ 8 hours 12 Reduction OK, Adhesion OK reduction OK Good stability Example 2 100 ℃ 8 hours 7 Reduction OK, Adhesion OK reduction OK Good stability Example 3 80 ℃ 8 hours 12 Reduction OK, Adhesion OK reduction OK Good stability Example 4 80 ℃ 3 hours 7 Reduction OK, Adhesion OK reduction OK Good stability Example 5 60 ℃ 8 hours 12 Reduction OK, Adhesion OK reduction OK Good stability Example 6 60 ℃ 4 hours 7 Reduction OK, Adhesion OK reduction OK Good stability Comparative Example 1 40 ℃ 4 hours 12 reduction No reduction Bad stability Bad Comparative Example 2 25 ℃ 12 hours 12 reduction Not perfect reduction Bad stability Bad

[0076] Referring to Table 1, it was confirmed that in Examples 1 to 6, the copper oxide on the surface of the internal electrode was stably reduced to copper, and the copper oxide inside the internal electrode was also reduced to copper. It was also confirmed that the crystal phase of the PZT-based ceramic was maintained excellently after reduction compared to before reduction.

[0077] On the other hand, in Comparative Example 1, which was wet processed at 40°C for 4 hours, no reduction occurred on the surface of the internal electrode, and in Comparative Example 2, which was wet processed at 25°C, it was confirmed that reduction did not occur well on the surface of the internal electrode, similar to Comparative Example 1.

[0078] Figure 4 shows photographs of the internal electrode before and after reduction according to Example 1, and SEM images. Figure 4(a) is an SEM image of the internal electrode cross-section of the ceramic laminate before reduction via a wet process, measured at 10.0 kV and magnified to 5,000x, showing copper oxide (Cu2O) before reduction. On the other hand, Figure 4(b) is an SEM image of the internal electrode cross-section of the laminated ceramic device after reduction via a wet process, measured at 10.0 kV and magnified to 5,000x, showing that copper oxide is reduced to copper and has a denser structure than the copper oxide before reduction, and that the PZT-based ceramic substrate is also maintained stably without deformation.

[0079] Figure 5 is a comparative photograph of the internal electrode when the time is changed while the wet process temperature according to Example 1 is fixed at 100 ℃. That is, based on the wet process conditions of Example 1, the surface of the internal electrode was examined by varying the stirring time while the temperature was fixed at 100 ℃. Figure 5(a) shows the wet process performed at 100 ℃ for 3 hours, Figure 5(b) shows the wet process performed at 100 ℃ for 6 hours, Figure 5(c) shows the wet process performed at 100 ℃ for 9 hours, Figure 5(d) shows the wet process performed at 100 ℃ for 12 hours, and Figure 5(e) shows the wet process performed at 100 ℃ for 12 hours. As shown in FIGS. 5(a), 5(b), 5(c), and 5(d), similar surface characteristics were observed when the wet process was carried out for a range of 3 to 12 hours, but it was confirmed that a somewhat different surface characteristic was observed in FIGS. 5(e), which was carried out for 24 hours at 100°C. Accordingly, it was found that it is desirable not to carry out the wet process for more than 12 hours.

[0080] Figure 6 is a kinetics graph according to pH change. Figure 6 was prepared by keeping only the wet process conditions (temperature, time, pH) of Examples 1 to 6 the same, and applying the copper composite compound of Preparation Example 2 as the internal electrode. Figure 6(a) shows a wet process temperature of 100 ℃, Figure 6(b) shows a wet process temperature of 80 ℃, and Figure 6(c) shows a wet process temperature of 60 ℃. The x-axis of Figure 6 represents the time for reacting the ceramic laminate by impregnating it with the base solution, and the y-axis represents the weight loss rate of the internal electrode. It is confirmed that stable results are shown under pH conditions of 7 and 12.

[0081] In summary, the present invention has the characteristic that the metal oxide can be reduced to a metal simply by manufacturing a ceramic laminate equipped with a metal oxide, preparing a base solution with a pH of 5 to 12 by mixing a chloride with an aqueous solvent, and then adding hydrazine hydrate (N2H4·H2O) and the ceramic laminate to the base solution and stirring the resulting wet solution at 60 to 100°C for up to 12 hours or less, while simultaneously stabilizing the PZT-based ceramic that serves as the substrate of the ceramic laminate without deformation.

[0082] According to these features, instead of the conventional dry heat treatment process in the presence of an inert gas at 300°C or higher, a wet heat treatment process based on an aqueous solvent is performed, which eliminates the need for additional hydrogen gas lines and large safety devices, thereby ensuring process stability and reducing associated costs. This is significant, and thus, there is an advantage in that mass production of multilayer ceramic devices is possible.

[0083] The foregoing description is merely an illustrative explanation of the technical concept of the present invention, and those skilled in the art to which the present invention pertains will be able to make various modifications and variations within the scope of the essential characteristics of the present invention. Accordingly, the embodiments disclosed in the present invention are intended to explain, not to limit, the technical concept of the present invention, and the scope of the technical concept of the present invention is not limited by such embodiments. The scope of protection of the present invention shall be interpreted by the claims, and all technical concepts within an equivalent scope shall be interpreted as being included within the scope of rights of the present invention.

Claims

Claim 1 A wet manufacturing method for a multilayer ceramic element, characterized by comprising: a step of manufacturing a ceramic laminate having a metal oxide and preparing a base solution having a pH of 5 to 12 by mixing a chloride with an aqueous solvent; a step of preparing a wet solution by adding hydrazine hydrate (N2H4·H2O) and the ceramic laminate to the base solution; and a step of reducing the metal oxide to a metal by stirring the wet solution at 60 to 100 ℃ for 3 to 12 hours. Claim 2 A wet manufacturing method for a stacked ceramic element according to claim 1, characterized in that the ceramic stack is manufactured by applying an electrode paste, prepared by mixing a metal with a binder, onto a PZT-based ceramic substrate to produce a ceramic sheet and stacking a plurality of said ceramic sheets; and degreasing and sintering the plurality of stacked ceramic sheets so that the metal is oxidized and formed into a metal oxide. Claim 3 A wet manufacturing method for a stacked ceramic element according to claim 1, characterized in that the wet solution is prepared by adding the hydrazine hydrate in a range of 0.01 to 10 moles based on 1 mole of the metal oxide. Claim 4 A wet manufacturing method for a multilayer ceramic element according to claim 1, wherein the chloride is one or more of sodium chloride (NaCl), potassium chloride (KCl), lithium chloride (LiCl), calcium chloride (CaCl2), and barium chloride (BaCl2). Claim 5 A wet manufacturing method for a stacked ceramic element according to claim 1, characterized in that, following the step of reducing to the metal, it further comprises the step of separating the ceramic stack from the wet solution and then washing and drying.

Citation Information

Patent Citations

  • Ceramic device using metal oxide and manufacturing method thereof

    KR1020200033167A